Sustained Inflammation Induced by LPS Leads to Tolerable Anorexia and Fat Loss via Tlr4 in Mice - Yang Y; Zhong W; Zhang Y; Cheng Y; Lai H; Yu H; Feng N; Han Y; Huang R; Zhai Q (Journal of Inflammation Research, 2022)
Yale Yang,1 Wuling Zhong,1 Yali Zhang,1 Yalan Cheng,1 Hejin Lai,1 Huimin Yu,1 Ning Feng,1 Yumo Han,2 Rui Huang,1 Qiwei Zhai1,2 1CAS Key Laboratory of Nutrition, Metabolism and Food Safety, Shanghai Institute of Nutrition and Health, University of Chinese Academy of Sciences, Chinese Academy of Sciences, Shanghai, People’s Republic of China; 2School of Life Science and Technology, ShanghaiTech University, Shanghai, People’s Republic of ChinaCorrespondence: Qiwei Zhai, Shanghai, 200031, People’s Republic of China, Tel +86 21 5492 0903, Fax +86 21 5492 0291, Email qwzhai@sibs.ac.cnBackground: Sustained inflammation is implicated in a variety of pathological conditions like infection, obesity and type 2 diabetes. Lipid metabolism is crucial to support immune response during infection of bacteria. However, how sustained inflammation affects lipid metabolism, especially in white adipose tissue remains largely unknown.Methods: Sustained inflammation was induced by daily injection of Lipopolysaccharide (LPS). Tlr4 knockout mice were used to study the mechanism. Inflammation and lipid metabolism were evaluated by quantitative PCR, white blood cell counting, nuclear magnetic resonance, fat cell size quantification, lipolysis and fatty acid uptake assays, respiratory exchange ratio, and energy expenditure.Results: Here, we found that sustained inflammation leads to fat loss in mice with a quick loss and gradual increase manner. Moreover, LPS injection leads to inflammation, anorexia, decreased lipid anabolism, and increased lipid catabolism. Mechanically, we show that LPS induces fat loss, inflammation, anorexia, and alteration of lipid metabolism mainly dependent on Tlr4. Interestingly, sustained inflammation induces less fat loss, especially in epididymal white adipose tissue, than pair-feeding, and pair-feeding has no significant effect on inflammation and leads to less fatty acid uptake, more lipid catabolism and energy expenditure than LPS injection. In addition, we demonstrate that short-term sustained inflammation leads to relative long-term tolerance for LPS-induced anorexia, inflammation and altered lipid metabolism.Conclusion: These findings demonstrate that sustained inflammation induced by LPS leads to tolerable anorexia and fat loss via Tlr4 in mice, and provide new insights into the effect of sustained inflammation on lipid metabolism and subsequent tolerance.Keywords: sustained inflammation, lipopolysaccharide, white adipose tissue, lipid metabolism, tolerance